EFFECT OF PLANT DENSITIES AND PHOSPHORUS LEVELS ON GROWTH AND YIELD OF GREEN GRAM (VIGNA RADIATA L.) - OWLA, R.L.; CHAVAN, B.N.; Singh, UMMED (Annals of Agricultural Research, 2014)
A field experiment was conducted on clay soil at the experimental farm of Department of Agronomy, Marathwata Agricultural University, Parbhani (Maharashtra).There were 12 treatment combinations replicated 4 times in split-plot design. The main plot treatments consisted of four combinations of two inter row (30 cm and 45 cm) and intra row (10 cm and 15 cm) spacings, while, the sub-plottreatments consisted of 3 levels of phosphorus viz., 25, 50 and 75 kg P2O5/ha.Application of 75 kg P2O5/ha significantly enhanced grain yield (8.97q/ha), straw yield (33.42q/ha), biological yield (42.61 q/ha) and protein content over 25 and 50 kg P2O5/ha.